Chieftains delivering : political determinants of capital spending in Ireland 2001-07 - Suiter, Jane (Trinity College (Dublin, Ireland). Department of Political Science, 2010)
This is a study about the allocation of resources in Ireland. It asks to what extent capital expenditure is allocated according to geopolitical or to policy considerations. In other words, to what extent do electoral calculations and to what extent does policy drive spending decisions? Many voters assume that governments do spend for partisan gain or in order to boost their re-election chances. Anecdotally, there is plenty of evidence, and legislators certainly indulge in a good deal of credit-claiming. Empirically, despite large-scale research elsewhere, to date there is no comprehensive spatial analysis of government spending in Ireland; indeed, there has been no systematic attempt to ascertain whether the Irish government engages in partisan spending. Theoretically, the literature argues that politicians will target either swing or core voters, depending on institutional incentives. However, this thesis argues that the incentives operating in Ireland will lead to a more personalist targeting of voters, with individual ministers or ‘chieftains’' likely to deliver significant additional resources to their own personal bailiwicks, while the governing party is likely to be unable or unwilling to target the areas of the party’s core electoral strength or swing voters. Chapter Two presents a systematic explication of the ways in which politicians pursue vote-buying strategies, from the US to the UK and beyond. It looks in detail at the institutional structures that incentivise different types of particularistic spending.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin